Hydrologic response characteristics of a tropical catchment to land use changes: a case study of The Nerus catchment - Hafizan, Juahir; Mohd Hafifi, Mat Nazir; Wan Nor Azmin, Sulaiman (2015)
Hydrologic response of a catchment with the most common expression through runoff coefficient reflects a complex response of interaction between the rainfall and catchment physical properties. In this study, an attempt has been made through the mean rainfall–runoff polygon method to explore the impact of land use change on the mean monthly runoff coefficient estimated from 27 years of the hydrology and land use records of a tropical catchment located in the east coast of Peninsular Malaysia. Specifically, the land use and flow records are divided into three intervals: (1982–1990), (1992–2000) and (2002–2010). The mean monthly rainfall–runoff polygon plotted is rendered to the three time intervals. The results have shown that contrasting shapes were computed which demonstrate the significant variability in the rainfall–runoff response characteristics under the linkage of land use changes. Ample information describing the hydrological responses of the study area has been attained through the quantitative approaches. The study has concluded that the rainfall–runoff polygon method can be used as a simple alternative method for assessing the impact of land use changes on the hydrological response.